2005
DOI: 10.1007/s00425-005-1509-5
|View full text |Cite
|
Sign up to set email alerts
|

Active anthocyanin degradation in Brunfelsia calycina (yesterday–today–tomorrow) flowers

Abstract: Anthocyanins are the largest group of plant pigments responsible for colors ranging from red to violet and blue. The biosynthesis of anthocyanins, as part of the larger phenylpropanoid pathway, has been characterized in great detail. In contrast to the detailed molecular knowledge available on anthocyanin synthesis, very little is known about the stability and catabolism of anthocyanins in plants. In this study we present a preliminary characterization of active in planta degradation of anthocyanins, requiring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
111
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 36 publications
0
111
0
1
Order By: Relevance
“…Very few data are available concerning the relationship between pigment degradation and petal color. Vaknin et al (2005) suggested that active anthocyanin degradation occurs in the petals of Brunfelsia calycina, resulting in white color. However, the precise mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Very few data are available concerning the relationship between pigment degradation and petal color. Vaknin et al (2005) suggested that active anthocyanin degradation occurs in the petals of Brunfelsia calycina, resulting in white color. However, the precise mechanism remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the breakdown of these molecules; although it has been shown that in some species, anthocyanin catabolism is a regulated process that is enzymatically catalyzed (Vaknin et al 2005). Analysis of some Arabidopsis mutants has suggested that active turnover and catabolism of phenylpropanoid intermediates may be common.…”
Section: à9mentioning
confidence: 99%
“…Anthocyanin accumulation is significantly induced in plants under stress conditions, such as high light intensity, low temperature, drought, or nutrition deficiency, and is degraded once the stress is eliminated (Winkel-Shirley, 2002;Rowan et al, 2009). Rapid anthocyanin degradation occurs in Brunfelsia calycina (yesterday-today-tomorrow) petals after flower opening (Zenner and Bopp, 1987;Vaknin et al, 2005). Anthocyanins are degraded during pear fruit maturity (Pyrus communis; Steyn et al, 2004) and throughout the senescence of litchi (Litchi chinensis; Zhang et al, 2001Zhang et al, , 2005 and blood citrus fruit (Barbagallo et al, 2007).…”
mentioning
confidence: 99%